Separation and anti‐inflammatory evaluation of phytochemical constituents from Pleurospermum candollei (Apiaceae) by high‐speed countercurrent chromatography with continuous sample load. Issue 13 (22nd May 2021) - Ali, Iftikhar; Mu, Yan; Atif, Muhammad; Hussain, Hidayat; Li, Jinping; Li, Dandan; Shabbir, Muhammad; Bankeu, Jean Jules Kezetas; Cui, Li; Sajjad, Shahida; Wang, Daijie; Wang, Xiao
Abstract: Pleurospermum (Apiaceae) species possess a wide range of biological properties viz. analgesic, anti‐inflammatory, antimalarial, and so on. Pleurospermum candollei (DC.) Benth. Ex C. B. Clark. is reported to cure diarrhea, gastric, respiratory, stomach, abdominal, joint, and back pain problems. In addition, it is also used for both male and female infertility. The present study deals with an efficient technique using high‐speed countercurrent chromatography for separation of chemical components from the methanol extract of P. candollei . Notably, nine main compounds namely luteolin 7‐ O ‐glucoside (1 ), oxypeucedanin hydrate (2 ), pabulenol (3 ), bergapten (4 ), heptadecanoic acid (5 ), ( E )‐isoelemicin (6 ), trans ‐asarone (7 ), α‐linolenic acid (8 ), and isoimperatorin (9 ) were very efficiently separated and isolated in pure form. Multiple injections were applied followed by two off‐line recycling high‐speed countercurrent chromatography. The inhibitory effect of nitric oxide production of all compounds was tested in the presence of 200 ng/mL lipopolysaccharide in RAW264.7 mice macrophage cells. The results demonstrated that compounds 7 and 8 effectively inhibited nitric oxide production, with IC50 values of 28.44 and 53.18 μM, respectively. This study thus validates the traditional claim of using P. candollei . Taken together, these findings will be useful in future research to find a potential candidate with anti‐inflammatory properties.